Storage of Simarouba amara Aubl. seeds - Santos, Jiovana Santos Pereira Amorim; Reis Mendonça, Andrea Vita; Carvalho, Edvania da Silva; Hora de Souza, Marcus Dhilermando; de Souza, Manuela Oliveira (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2021)
Prior knowledge about the physiological behavior of seeds under storage conditions allows the use of appropriate techniques to maintain viability. The goal of the present study was to classify the behavior of Simarouba amara seeds regarding their physiological potential during storage. The seeds were obtained from mature fruits, collected from five parent plants located at the Joanes-Ipitanga Environmental Protection Area (EPA) (Simões Filho, Bahia) in January 2018. Two experiments were carried out in a completely randomized design. In the first one, seed desiccation tolerance was evaluated with seven moisture contents: 5%, 7.5%, 10%, 12.5%, 15%, 25% and 35.6% (initial moisture). A germination test was carried out to evaluate the seeds’ vigor. In the second experiment, the seeds were stored with moisture contents of 7.5%, 12.5% and 35.6% at temperatures of 8 °C, 15 °C and 20 °C) for two storage periods, two and four months, and samples were taken to determine moisture content and conduct the germination test. Germination tests were performed in BOD chambers at 30 °C and with 12-hour light photoperiod. Daily counts were performed for the number of germinated seeds. We measured germination percentage, mean germination time, uncertainty index, percentage of normal seedlings, and percentage of unviable seeds. Simarouba amara seeds tolerate desiccation up to 7.5% moisture content, but lost viability when stored under this condition. At four months of storage all seeds lost viability. Simarouba amara seeds are recalcitrant and lose viability before reaching two months of storage.
Keywords: Desiccation tolerance; Seed conservation; Recalcitrant